The effects of diet form and feeder design on the growth performance of finishing pigs - Myers, A.J.; Bergstrom, J.R.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 1,146 growing pigs (PIC 1050 × 337, initially 85.8 lb) were used in a 104-d study to evaluate the effects of diet form (meal vs. pellet) and feeder design (conventional dry vs. wet-dry) on finisher pig performance. The treatments were arranged in a 2 × 2 factorial with 11 replications per treatment and 25 to 27 pigs per pen. Half of the pens were equipped with a 5-hole conventional dry feeder and the other half had a double-sided wet-dry feeder. All pigs were fed a corn-soybean meal-based diet containing 20% dried distillers grains with solubles (DDGS) during the first 4 dietary phases and 10% DDGS in phase 5. The only difference in diet among treatments was diet form (meal vs. pellet). Pen weights and feed disappearance were measured on d 0, 14, 28, 42, 56, 70, 86, and 104. Pictures of feeder pans were taken once during each phase and evaluated by a panel of 4 individuals for percentage pan coverage. From d 0 to 28, no diet form × feeder design interaction was observed for ADG or F/G. Pigs fed pelleted diets had poorer (P < 0.001) F/G compared with those fed meal diets, which appeared to be due to poor pellet quality (39.6% fines). From d 42 to 86, pellet quality improved (4.4% fines), and a diet form × feeder interaction (P < 0.02) was observed for ADG, whereas pigs presented meal diets in a dry feeder had decreased ADG compared with pigs presented pelleted diets in dry feeders or pigs presented feed via wet-dry feeders regardless of diet form. Pigs presented pelleted diets had improved (P < 0.001) F/G compared with those fed meal diets. Pigs fed via wet-dry feeders had increased (P < 0.03) ADFI and poorer F/G compared with pigs with dry feeders. Overall, pigs fed with wet-dry feeders had increased (P < 0.02) ADG and ADFI, and poorer F/G compared with those with dry feeders, whereas pigs presented pelleted diets had a tendency for improved (P < 0.06) F/G compared with those presented meal diets. In conclusion, regardless of diet form, pigs fed from wet-dry feeders had increased ADG and ADFI compared with pigs fed via dry feeders. Additionally, pellet quality appeared to influence responses because pigs provided higher-quality pellets via dry feeders had increased growth performance compared with pigs fed meal diets. Conversely, if pellet quality was poor, feed efficiency benefits associated with pelleting were lost.
Keywords: Swine; Feeder; Finishing pig; Growth; Pelleting